Hearing rehabilitation in Treacher Collins Syndrome with bone anchored hearing aid - Polanski,José Fernando (2015)
Objective: To describe a case of hearing rehabilitation with bone anchored hearing aid in a patient with Treacher Collins syndrome. Case description: 3 years old patient, male, with Treacher Collins syndrome and severe complications due to the syndrome, mostly related to the upper airway and hearing. He had bilateral atresia of external auditory canals, and malformation of the pinna. The initial hearing rehabilitation was with bone vibration arch, but there was poor acceptance due the discomfort caused by skull compression. It was prescribed a model of bone-anchored hearing aid, in soft band format. The results were evaluated through behavioral hearing tests and questionnaires Meaningful Use of Speech Scale (MUSS) and Infant-Toddler Meaningful Auditory Integration Scale (IT-MAIS). Comments: The patient had a higher acceptance of the bone-anchored hearing aid compared to the traditional bone vibration arch. Audiological tests and the speech and auditory skills assessments also showed better communication and hearing outcomes. The bone-anchored hearing aid is a good option in hearing rehabilitation in this syndrome.